Entrepreneurship education and personality traits as predictors of entrepreneurial intention: A qualitative approach - Anita Bans-Akutey (Annals of Management and Organization Research, 2022)
Purpose: The study explored entrepreneurship education and personality traits as predictors of entrepreneurial intention among final-year undergraduate students of a private institution in Ghana. Research methodology: A qualitative research approach was used in a case study design for this research. A purposive sampling technique was used to collect data from final-year students pursuing an undergraduate program in Information Technology from a private tertiary institution in Ghana. Observation and focus group discussions were used to collect data over a period of ten weeks. Results: Results indicated that though all students were exposed to the same tuition, course content and assessments; the level of entrepreneurial intention varied. Some groups of students wanted to pursue entrepreneurial ventures immediately after school; others wanted to start a business venture while they were still in school pursuing their first degree. Another set preferred to work as employees for a few years before pursuing entrepreneurship. The final group preferred to be employed throughout their working life with the aim of rising through the ranks as employees; with all the various groups showing a variety of personality traits. Limitations: The study was limited to final-year undergraduate students of a private institution in Ghana. Contribution: Educators, who specialize in training students in entrepreneurship need to focus more on orienting students to effectively manage their individual personality traits in ways that will ensure successful entrepreneurship careers. Novelty: This study qualitatively shows the varied levels at which entrepreneurship education affects students’ entrepreneurial intentions based on their personality traits.